Micropapillary variant of transitional cell carcinoma in a young adult: a rare case report - Barua, Sasanka Kumar; Ghanghoria, Ashish; Baruah, Saumar Jyoti; P., Rajeev T.; Bagchi, Puskal Kumar; Sarma, Debanga; Phukan, Mandeep (International Surgery Journal, 2019)
Micropapillary carcinoma is an uncommon variant of urothelial carcinoma with high metastatic potential. Usually seen in elderly individual, we herein report a case of 42 years old man presented with macroscopic hematuria for 1 month. Evaluation with CECT whole abdomen revealed irregularly marginated hyperattenuated mildly enhancing intraluminal mass lesions in right lateral wall and in floor of urinary bladder. No perivesical infiltration and no regional lymphadenopathy were detected. TURBT done and subsequent histopathological examination showed a high-grade transitional cell carcinoma with micropapillary variant. He was subjected to radical cystoprostatectomy with pelvic lymph node dissection. The pathological examination revealed a high-grade transitional cell carcinoma with micropapillary variant invading the perivesical adipose tissue. No tumor recurrence or metastasis was reported at the 18-months follow-up.